Optimization of Flexible Room Divider Usage in SLB-C Karya Bhakti Classrooms: An Approach to Learning Patterns for Children with Intellectual Disabilities - Putri, Alisa Dwi; Soewardikoen, Didit Widiatmoko; Azhar, Hanif; Nurhadiansyah, Mahendra (Gorga : Jurnal Seni Rupa, 2025)
This research endeavors to address the challenges faced by Special Learning Centers (SLBs), particularly SLBs-C, which operate in limited spaces and utilize room dividers to separate classrooms. The utilization of these dividers presents limitations and impedes the learning process for children with intellectual disabilities. This study adopts a design thinking methodology, focusing on the observations and requirements for flexible spaces at SLB-C Karya Bhakti. Data collection involved stakeholder interviews, questionnaires, visual observations, and a literature review. The gathered data was subsequently analyzed through a SWOT analysis and organized using a mind-mapping technique to develop a design concept for an optimal room divider that enhances room flexibility. The identified challenges served as the foundation for an iterative design process, resulting in a product tailored to the specific needs of SLB-C Karya Bhakti. This product underwent validation with stakeholders and experts before its implementation. The outcome of the design is a recommendation for optimizing the use of room dividers with materials and designs that cater to the requirements of children with intellectual disabilities. The implementation of an optimized room divider has demonstrated a positive impact on the concentration of children with intellectual disabilities, enhancing the teaching and learning process.